2019
DOI: 10.1108/itp-05-2018-0251
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cybercrimes in smart cities of India: from a citizen’s perspective

Abstract: Purpose The purpose of this paper is to identify the factors influencing the citizens of India to prevent cybercrimes in the proposed Smart Cities of India. Design/methodology/approach A conceptual model has been developed for identifying factors preventing cybercrimes. The conceptual model was validated empirically with a sample size of 315 participants from India. Data were analyzed using structural equation modeling with SPSS and AMOS softwares. Findings The study reveals that the “awareness of cybercri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 97 publications
(134 reference statements)
1
35
0
Order By: Relevance
“…This relates to data already present within city databases but also the linking of data with new systems and sensors present within the smart city, that impact security and privacy (Van Zoonen 2016 ). The threats stemming from information security, data privacy and cyber-related factors where unauthorised access to information can cause undesired consequences, highlights the criticality of addressing these issues early within the design and development stage of smart cities (Chatterjee et al 2019 ; Elmaghraby and Losavio 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This relates to data already present within city databases but also the linking of data with new systems and sensors present within the smart city, that impact security and privacy (Van Zoonen 2016 ). The threats stemming from information security, data privacy and cyber-related factors where unauthorised access to information can cause undesired consequences, highlights the criticality of addressing these issues early within the design and development stage of smart cities (Chatterjee et al 2019 ; Elmaghraby and Losavio 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the use of personal tools for work also increases the risk that devices will be lost or stolen ( Jones & Chin, 2015 ; Nokia, 2019 ; Tu, Turel, Yuan, & Archer, 2015 ), endangering organizational data ( Baillette et al, 2018 ). Third, smartphones have become a lucrative target for cybercriminals ( Chatterjee, Kar, Dwivedi, & Kizgin, 2019 ; Checkpoint, 2020 ), and corporate data can be corrupted by attacks through hacked or malware-infected smartphones. Fourth, since employees own the devices, their run greater risks when using BYOD than they do when using corporate tools ( Hovav & Putri, 2016 ) or computers ( McGill & Thompson, 2017 ; Thompson et al, 2017 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a study of early users of smartphone banking services, Susanto et al (2015) found that after the initial use ( trial ) of the banking services, the critical antecedents of usage continuance were user satisfaction and self-efficacy . A survey that assessed Taiwanese residents' willingness to continue using SCS confirmed that they were willing to continue only if they perceived the services to be “designed with innovative concepts that secure their privacy and offer a high quality of services” (Yeh, 2017; Chatterjee et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Smart city service channels and tools, such as ATMs, e-Kiosks, smartcards, and mobile applications have not always enjoyed good acceptance in many markets due to users' concerns about security and privacy issues (Belanche-Gracia et al , 2015; Chatterjee et al , 2018). Also, the fact that smart services are accessed remotely using machine-mediated channels makes it worrisome for many users with regard to confidentiality issues, specifically in the healthcare sector, where personal contact with service providers is preferred by patients (Wunderlich, 2013).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%